PENGARUH PELATIHAN BAYANGAN (SHADOW) BULUTANGKIS TERHADAP PENINGKATAN KELINCAHAN DAN KECEPATAN REAKSI - Arya Kusuma, Gusti Ngurah (Jurnal Ilmu Keolahragaan Undiksha, 2013)
The purpose of  this research was to find out the effect of badminton shadow training  toward the  increased agility and  speed of  reaction. The type of  research  was a quasi-experimental and  the design of  research  was  the  non-randomized  pretest-posttest control group design. The subjects were  man’s  student badminton extracurricular participants  of SMAN 4 Singaraja.  Agility and speed of  reaction posttest to the treatment group and the control group were analyzed  by  independent  t-test at significance  0,05 with SPSS 16.0.  Based  on independent t-test results were showed : (1) to the agility variable, the comparison of the treatment and the control group values ​​obtained t = 2,724, with a significance value of 0,011, (2) to the speed of reaction variable, the comparison of the treatment and the control group values ​​obtained t = 2,524, with a significance value of 0,018. Calculated significance value smaller than the value of 0,05 (Sig < 0.05), thus the research hypothesis "badminton shadow training affect the increased agility and reaction speed in badminton extracurricular participants of SMAN 4 Singaraja " was received. From the analyzed and discussion were concluded that : (1) badminton shadow training effect the increased agility in badminton extracurricular participants of SMAN 4 Singaraja, (2) badminton shadow training effect the increased reaction speed in badminton extracurricular participants of  SMAN 4 Singaraja.